The role of atomic scale segregation in designing highly ductile magnesium alloys. (1st September 2016) - Basu, I.; Pradeep, K.G.; Mießen, C.; Barrales-Mora, L.A.; Al-Samman, T.
Abstract: Two solid solution binary magnesium-rare earth (RE) alloys, Mg-1wt.% Gd and Mg-1wt.% Dy were subjected to large strain hot rolling followed by recrystallization annealing at different temperatures for 60 min. Recrystallization and grain growth in Mg-1Gd led to stepwise change in the deformation texture, highlighted by a complete disappearance of the basal texture component developed during rolling. In case of Mg-1Dy, texture changes upon annealing were less accentuated, characterized by gradual softening of the deformation basal texture with increasing annealing temperatures. The development of favorable RE-textures during annealing is believed to be a result of solute segregation to planar defects, such as grain boundaries. It was observed using atom probe tomography that Gd atoms show a much higher grain boundary segregation tendency than Dy atoms. The enhanced segregation behavior of Gd manifests during annealing into a strong growth advantage of recrystallized off-basal orientations over basal orientations originating from the deformation microstructure, continuing as discontinuous grain growth at higher annealing temperatures and longer durations. No distinctive growth advantage was witnessed during recrystallization and grain growth of Mg-1Dy. Different segregation effects between the two RE elements and the resulting annealing texture evolution strongly impacted the room temperature tensile ductilities of both alloys. Mg-1Gd seemed to exhibit concomitant precipitation hardening effects, thereby displaying higher tensile strength along with enhanced ductilities. This work demonstrates the exciting possibility of being able to selectively exploit grain boundary characteristics using RE elements as an effective mechanism to tailor the microstructure during thermomechanical processing, thereby improve the mechanical performance of Mg alloys. Graphical abstract: